Association of prognostic fa ctors with overall survival in myelodysplastic syndromes: a cohort study - Sotirova, Tatjana; Genadieva Stavrikj, Sonja; Krstevska Balkanov, Svetlana; Pavkovikj, Marica; Amzai, Gazmend (SHMSHM - AAMD, 2015)
Background: Myelodysplastic syndromes (MDS) are heterogeneous disorders in terms of clinical presentation, laboratory findings and life expectancies. A lot of studies have been conducted to determine factors that can refine the prediction of prognosis in MDS. Aim: Our aim was to evaluate which prognostic factors had an impact on overall survival (OS) in MDS. Methods: we conducted retrospective cohort study of 154 adult patients (81 male, 73 female) with MDS who presented to the University Clinic of Hematology, Ss Cyril and Methodius University, Skopje, Macedonia, from January 2011 to June 2014. Data on demographics, FAB classification, treatment and outcome were collected. Results: Age and gender had no influence on OS (p=.80847 and p=.974895, respectfully). Different FAB subtypes had an impact on OS (p = .00757). Bone marrow (BM) blast percentage correlated significantly with OS (p= .028026). Hemoglobin, platelet count and absolute neutrophil count (ANC) did not influence OS (p=. 179970, p= .386355 and p= .972602, respectfully). Transfusion did not influence OS (p= .445856). Albumins had no impact on OS (p=.559900). Lactate dehydrogenase (LDH) and comorbidities influenced OS (p= .018895 and p= .02278, respectfully). Leukemic transformation was noticed in 7 (4.5%) patients. Mortality was 35.1%. Conclusions: FAB subtypes, BM blast percentage, LDH and comorbidities are independent predictors on OS and should be considered for future revisions of International Prognostic Scoring System in order to refine the prediction of prognosis in MDS.
Keywords: myelodysplastic syndromes; overall survival; prognostic factors